Une progressive végétalisation des projets d’aménagement répond-elle aux enjeux de l’urbanisme durable ? Le cas de Lausanne - Fabien Jakob (Belgeo)
Focusing on the participatory revision of the master and land-use plans for the city of Lausanne, this research aims to understand how natural elements, and plants in particular, are taken into account in governance mechanisms, strategies for adapting urban spaces to the impacts of climate change, and regulatory and technical instruments for public action in territorial planning and management.